Immediate Effect of Elastic Taping Application on Gait Functional Ability in Patients with Stroke - Rahadi Arie Hartoko (Alami Journal (Alauddin Islamic Medical) Journal, 2021)
Background: The typical consequence of a stroke is the limitation in walking ability. In stroke patients, there is a disruption of mobilization, including walking. Stroke patients exhibit abnormal walking patterns as compensation for muscular weakness. Elastic taping known to increase functional movement through increased muscle strength In addition; elastic taping helps maintain muscle coordination of agonists, synergists, and antagonists. Objective: Determine the immediate effect of elastic tape on the gait functional ability in post stroke patient with ankle dorsiflexor muscle weakness. Method: This research is an experimental pre-post study. The total subjects are 11 patients with hemiparesis following stroke. The gait speed, step length and stride length measured by gait analysis lab with CMAX gait software, before and after the elastic tape application for 30 minutes. Leukotape K® was applied with facilitation technique on the anterior tibial and extensor digitorum longus, from the origin to the insertion with 100% of stretch. Result: The gait speed and step length on healthy side after 30 minutes elastic tape increased when compared with the pre-application value (p>0.05). Conclusion: There is an increment of gait speed and step length on healthy side in post-stroke patients with ankle dorsiflexor weakness after 30 minutes elastic taping application. Elastic taping may be beneficial in treating gait functional disturbances in post-stroke patients.